How Did al-Suyuti Abridge Ibn Taymiyya’s Nasihat Ahl al-Iman fi al-Radd ‘ala Mantiq al-Yunan? - Mufti Ali (Al-Jami'ah: Journal of Islamic Studies, 2008)
Al-Radd ‘ala ’l-Mantiqiyyin (an alternative title for Nasihat Ahl al-Iman) is a work composed by Ibn Taymiyya to demolish each principle of logic as well as to unravel the depravity of their foundation. Probably due to Ibn Taymiyya’s being genius, when he destroys those principles, he could not avoid himself to discuss digressively irrelevant topics dealing with theological as well as metaphysical issues. In a number of passages in al-Radd, he could not even hinder himself to make a good deal of repetitions. Therefore, al-Radd ‘ala’l-Mantiqiyyin is complex and difficult to use. The coherence of arguments that Ibn Taymiyya formulated is not solid and comprehensive. His criticism of logic is not penetrating as well. On the basis of my analysis of al-Suyuti’s method of abridgement of Ibn Taymiyya’s al-Radd, I argue that al-Suyuti succeeded in rendering Ibn Taymiyya’s sequence of ideas superior to that found in the original work of the latter. The result of this study confirms Hallaq’s argument that the overall result of al-Suyuti’s abridgement of Ibn Taymiyya’s al-Radd is ‘a more effective critique of logic than that originally formulated by Ibn Taymiyya